Pembuatan Animasi 3D Pengolahan Kelapa Sawit menjadi Minyak Mentah Kelapa Sawit menggunakan Metode MDLC - Andri Nofiar (Computer Science and Information Technology, 2022)
Current technological developments make it easier for people to find information using communication tools such as smartphone, computers, and televisions,but many people don’t understand how the process of processing palm oil into crude palm oil. In making animation processing palm oil into crude palm oil, the information is still in the form of text, and still little information in form video. The method used in this research is Multimedia Development Life Cycle (MDLC) which consist of concept, design, material collecting, assembly, testing, distribution is made using Blender software versi 2.9, dan Adobe Premiere Pro cc2017. This 3D animation will be used for the banefit of community in understanding the process of processing palm oil into crude palm oil. The result of this study are 3D animated videos in format MP4.